DIFFERENCE IN SIZE OF LEPROSY PEDIS ULCER INJURY BEFORE AND AFTER THERAPY AT LEPROSY HOSPITAL DONOREJO, JEPARA REGENCY - Pramesti Widya Kirana; Muslimin Muslimin; Teddy Wahyu Nugroho; Reni Yuniati (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: Leprosy sufferers who experience disability at the time of diagnosis are usually late in seeking treatment because they are less aware of their health. Central Java Province ranks third with new cases of leprosy as many as 1,644 cases, after East Java (3,373), West Java (1,813) Provinces. It can be concluded that in Central Java there are still new cases of leprosy that if not treated properly will cause disabilities. Thus, level 2 disabilities in the form of foot ulcers should always be monitored and treated properly. Aim: Observe the success rate of several types of therapy for leprosy with foot ulcer at Donorejo Kelet Leprosy Hospital in Jepara Regency, and identify the grade and depth of ulcers before and after therapy. Method: Descriptive observational research (case study) using primary data obtained from questionnaires and weekly evaluation results regarding the size development of foot ulcers in leprosy for 4 weeks. Secondary data in the form of the given therapy were obtained from medical records. Data collected was processed descriptively covering general data such as age, sex, nutritional status, and special data including the patients’ risk factors (history of smoking, hygiene, wound size in centimeters (numerical data)). The data obtained were then compared between before and after therapy, and were analyzed with each other. Result: There were nine cases of leprosy with a foot ulcer, consisting of eight male patients and one female patient. The most common risk factor is smoking. After the leprosy patients were being treated for four weeks conventionally (wearing footwear, dressing, wound hygiene) and pharmacologically, there was a significant change in the reduction in wound volume with p=0.008 (p<0.05).